Triboelectric material and preparation method and application thereof

By using TS-CFP triboelectric materials combined with SiO2 nanoparticles and Ti3C2Tx dispersion in a triboelectric generator (TENG), the problems of improving TENG's electrical output performance and triboelectric charge storage are solved, and efficient and stable electrical output performance is achieved.

CN119431895AActive Publication Date: 2025-02-14GUANGXI UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411574943.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

There is room for improvement in the electrical output performance of existing tribo nanogenerators (TENGs), especially in terms of tribocharge storage and dissipation rates, which are difficult to achieve large-scale commercial applications.

Method used

By attaching SiO2 nanoparticles to the cellulose framework and combining them with Ti3C2Tx dispersion, Ti3C2Tx-SiO2-CFP (TS-CFP) triboelectric material is formed, and SiO2 is used as a deep trap builder to enhance the storage and transfer of friction charges. .

Benefits of technology

While maintaining the energy conversion efficiency of TENG, it can significantly improve the electrical output performance and stability, reduce the dissipation rate of friction charge, improve the charge storage capacity of friction electrical materials, and ensure the efficient and stable output of TENG.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431895A_ABST
    Figure CN119431895A_ABST
Patent Text Reader

Abstract

The invention discloses a triboelectric material and a preparation method and application thereof, and belongs to the technical field of friction materials. The preparation method of the triboelectric material comprises the following steps: adhering SiO2 to a cellulose skeleton to obtain a cellulose material adhered with SiO2; and adding a Ti3C2Tx dispersion liquid to the cellulose material attached with SiO2, and drying to obtain the triboelectric material. The Ti3C2Tx-SiO2-CFP (TS-CFP) prepared by the invention can promote more triboelectric charges to be transferred into the material and firmly capture the charges in a deep trap to prevent the charges from being dissipated, so that high-output and durable TENG is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of friction materials, and in particular to a triboelectric material and a preparation method and application thereof. Background Art

[0002] In the context of "intelligence" becoming the main development trend of all walks of life in today's society, various new sensors that are sensitive to environmental factors such as temperature, humidity, gas, light, pressure, microorganisms and pH are increasingly used in packaging materials and containers, and have promoted the rapid development of smart packaging. At the same time, the power supply and endurance of sensors have also become a hot spot and difficulty in the design of smart packaging systems. As an emerging energy conversion technology, the friction nanogenerator (TENG) can effectively convert mechanical energy into electrical energy by coupling contact electrification (CE) and electrostatic induction effects. With its advantages of flexible structural selection, wide material selection, low cost and easy manufacturing, it has shown great application potential in the field of energy harvesting and is expected to provide an effective solution to the power supply and endurance problems of intelligent and miniaturized sensors. However, how to improve the electrical output performance of TENG and realize large-scale commercial applications is still a huge challenge.

[0003] In existing studies, the problem of delaying the decay of triboelectric charge is often overlooked, but it is also a potential strategy to further improve the output of TENG in the future. The key lies in the improvement of the ability of triboelectric materials to store triboelectric charge. Researchers have optimized the storage process of triboelectric charge by preparing a rhombic perovskite array structure to regulate the dielectric properties of the friction material. However, the preparation process is relatively complicated and requires high-precision processing equipment and technology. In addition, it is also possible to introduce a built-in electric field into the friction material through doping, interface engineering and other technologies to inhibit the recombination of triboelectric charge with the induced charge on the electrode surface and increase the storage depth and storage amount of triboelectric charge. However, this requires a deep understanding of the interaction mechanism between materials, which is difficult. In addition, the regulation process may require special treatment or modification of the material, which is relatively costly. Compared with these, the high-pressure treatment process is relatively simple and low-cost, and can improve the charge storage capacity by changing the microstructure and electronic structure of the material. However, it may have a certain impact on the overall performance of the material (such as mechanical properties, thermal stability, etc.). Therefore, in order to reduce triboelectric charge loss while maintaining the energy conversion efficiency of TENG, new charge storage technologies must be developed and studied. Summary of the invention

[0004] The purpose of the present invention is to provide a triboelectric material and a preparation method and application thereof, so as to solve the problems existing in the above-mentioned prior art.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] One of the technical solutions of the present invention: a method for preparing a triboelectric material, comprising the following steps:

[0007] Attaching SiO2 to a cellulose skeleton to obtain a cellulose material attached with SiO2;

[0008] Adding Ti3C2T to the cellulose material with SiO2 attached x The dispersion is vacuum filtered and dried to obtain the triboelectric material (i.e., Ti3C2T x -SiO2-CFP, referred to as TS-CFP).

[0009] Furthermore, the method of attaching SiO2 to a cellulose skeleton comprises the following steps:

[0010] SiO2 is added into water and ultrasonically dispersed to obtain a SiO2 dispersion, the SiO2 dispersion is poured onto a cellulose material, and the cellulose material with SiO2 attached is obtained after vacuum filtration.

[0011] Furthermore, the SiO2 is nano-SiO2 with a particle size of 10 nm;

[0012] The dosage ratio of SiO2 to water is 0.0075 mg:30 mL; the dosage ratio of SiO2 dispersion to the area of ​​cellulose material is 30 mL:12.56 cm 2 .

[0013] Furthermore, the SiO2 and Ti3C2T in the SiO2 dispersion x Ti3C2T in dispersion x The mass ratio is 0.0075mg:3mg; the cellulose material includes filter paper.

[0014] The second technical solution of the present invention: a triboelectric material prepared by the above preparation method.

[0015] The third technical solution of the present invention: an application of the above-mentioned triboelectric material in the preparation of a triboelectric nanogenerator.

[0016] Technical solution 4 of the present invention: a triboelectric nanogenerator (TENG), using the above-mentioned triboelectric material as a friction layer.

[0017] New two-dimensional material Ti3C2T xIt has abundant surface terminations (-O, -OH, -F) and has the characteristics of attracting and quickly transmitting electrons. When applied to the friction layer of TENG, it can transfer more friction charges to the interior of the material during the contact-separation cycle. As a typical inorganic electret, SiO2 has a certain binding energy level, can effectively capture charges, and simultaneously improve the positive and negative properties of triboelectricity, so that it can be matched with a variety of materials without being limited to a specific triboelectric pair. The present invention introduces SiO2 into Ti3C2T x The interface with cellulose filter paper makes Ti3C2T x The interaction effect with SiO2 constitutes a "transmission channel" that promotes the transfer of triboelectric charges to the interior of the material while firmly capturing the charges in the "trap structure" to prevent their dissipation, thereby obtaining a high-output, durable TENG.

[0018] The present invention discloses the following technical effects:

[0019] (1) Ti3C2T prepared by the present invention x -SiO2-CFP (TS-CFP) can promote more triboelectric charge transfer to the interior of the material while firmly capturing the charges in deep traps to prevent their dissipation, and can be used for the preparation of high-output and durable TENG.

[0020] (2) The present invention uses a vacuum-assisted filtration method to utilize the large energy gap (7.6 eV) of SiO2 to deposit Ti3C2T x Deep traps were introduced into the interface of cellulose (filter paper) to prepare a new triboelectric material, which improved the electrical output performance of TENG. The performance measurement results showed that the normalized ISPD curve of TS-CFP showed a lower charge dissipation rate than that of pure cellulose (filter paper). The trap energy level density distribution showed that the deep trap density of the triboelectric material (TS-CFP) introduced with SiO2 increased from 0.020×10 21 eV -1 ·m -3 to 1.089×10 21 eV -1 ·m -3 The increase is about 53 times, which is because the increase in trap density and depth can enhance the material's charge capture ability and inhibit charge migration.

[0021] TS-CFP and polyperfluoroethylene propylene (FEP) were used as a triboelectric pair and assembled into TENG. The electrical output performance test showed that the maximum output power of TS-CFP-based TENG increased by more than 61 times compared with pure fiber-based TENG, and it still had a stable voltage output of up to 136V after 20,000 contact and separation cycles. In addition, the triboelectric humidity sensor based on TS-CFP can accurately detect humidity changes in the range of 45-95% RH, showing an excellent linear correlation (R 2 =0.992).

[0022] (3) The present invention increases the charge storage capacity of the triboelectric material and reduces the dissipation rate of the triboelectric charge by adjusting the preparation method and introducing deep traps, thereby ensuring the high efficiency and stability of the TENG electrical output performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 Schematic diagram of the implementation strategy of the triboelectric material (TS-CFP) prepared in Example 1, wherein a is a preparation flow chart, b is a bonding action schematic diagram, and c is a charge transport and storage schematic diagram;

[0025] Figure 2 The defect states of the qualitative filter paper (CFP), the T-CFP prepared in Comparative Example 1, and the triboelectric material (TS-CFP) prepared in Example 1 are characterized, wherein a is the FTIR spectrum, b is the XRD spectrum, c is the Raman spectrum, d is the XPS full spectrum, e is the C1s spectrum, f is the Si 2p spectrum of TS-CFP, g is the HRTEM image of the TS-CFP dispersion, and h is the Ti3C2T in the TS-CFP dispersion. x lattice spacing;

[0026] Figure 3 Ti 2p spectrum of the triboelectric material (TS-CFP) prepared in Example 1;

[0027] Figure 4The triboelectric dissipation and storage performance of the qualitative filter paper (CFP), the T-CFP prepared in Comparative Example 1, and the triboelectric material (TS-CFP) prepared in Example 1 are shown in FIG. 1 , wherein a is the normalized ISPD curve (isothermal surface potential decay curve), b is the shallow well energy level distribution, c is the deep well energy level distribution, d is the dielectric constant, e is the dielectric loss, f is the dynamic conductivity, and g is the surface potential distribution;

[0028] Figure 5 The triboelectric properties of TENG prepared with different triboelectric materials (qualitative filter paper (CFP), T-CFP prepared in Comparative Example 1, and triboelectric material (TS-CFP) prepared in Example 1), wherein a is the charge density of different devices, b is the short-circuit current of different devices, c is the open-circuit voltage of different devices, d is the roughness comparison of different friction layers, e is the open-circuit voltage of TS-CFP at different SiO2 addition amounts, f is the output stability of TS-CFP-based TENG after 20k contact-separation cycles, g is the output voltage of TS-CFP-based TENG at different contact-separation frequencies, h is the power density of different devices, and i is the charging behavior of TS-CFP-based TENG;

[0029] Figure 6 The output voltage and current of TENG prepared with different triboelectric materials (qualitative filter paper (CFP), T-CFP prepared in Comparative Example 1, and triboelectric material (TS-CFP) prepared in Example 1) change with load resistance, where a is the change of output voltage with load resistance, and b is the change of current with load resistance;

[0030] Figure 7 The application of TENG prepared with different triboelectric materials (qualitative filter paper (CFP), T-CFP prepared in comparative example 1, triboelectric material (TS-CFP) prepared in example 1) in extreme climate, wherein a is a schematic diagram of energy harvesting and humidity sensing of TS-CFP-based TENG under hot conditions, b is the voltage of CFP-based TENG under ultraviolet irradiation for different time periods, c is the voltage of TS-CFP-based TENG under ultraviolet irradiation for different time periods, d is the output voltage of TS-CFP-based TENG under different heating temperatures, e is the voltage of TS-CFP-based TENG under heating for different time periods at 230°C, f is the sensitivity of TS-CFP-based TENG as a sensor, g is the linear relationship between TS-CFP-based TENG and humidity, and h is the real-time output voltage of TS-CFP-based TENG;

[0031] Figure 8 is the voltage of T-CFP-based TENG under ultraviolet irradiation for different time periods;

[0032] Fig. 9Ultraviolet transmission spectra of the qualitative filter paper (CFP), the T-CFP prepared in Comparative Example 1, and the triboelectric material prepared in Example 1 (TS-CFP). DETAILED DESCRIPTION

[0033] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0034] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0035] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0036] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0037] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0038] The nano-SiO2 used in the present invention is high-purity nano-SiO2 with a purity of more than 99.9% and a particle size of 10 nm, purchased from Zhejiang Bohuasi Nanotechnology Co., Ltd.; Ti3C2T x (x is surface functional groups such as -OH, -O, -F and -Cl) monolayer solution (0.5 g / 100 mL) was purchased from Zhejiang Ningbo Jinlei Nanomaterial Technology Co., Ltd.; qualitative filter paper (diameter = 7 cm, medium speed) was purchased from Hangzhou Special Paper Co., Ltd.; FEP film was purchased from Guangzhou Polyfluoride New Material Technology Co., Ltd.; the water used was deionized water (DI).

[0039] Example 1

[0040] A triboelectric material (Ti3C2T x -SiO2-CFP) preparation method:

[0041] (1) Add nano-SiO2 to deionized water (DI) (the dosage ratio of nano-SiO2 to deionized water is 0.0075 mg:30 mL), and then use a cell disruptor to perform ultrasonic dispersion to obtain a SiO2 dispersion.

[0042] (2) Place a qualitative filter paper with a diameter of 7 cm in a sand core funnel (funnel diameter is 4 cm), turn on the vacuum pump switch, and then drip deionized water (DI) to make the qualitative filter paper and the sand core funnel tightly connected. Take 30 mL of SiO2 dispersion and pour it directly into the filtration device. After the water is drained, continue to filter for 10 minutes to allow the SiO2 nanoparticles to adhere to the cellulose skeleton (qualitative filter paper) to obtain a cellulose material with SiO2 attached.

[0043] (3) Take 0.6 mL of Ti3C2T with a concentration of 5 mg / mL x Dispersion, dilute it to 0.2 mg / mL with deionized water DI. Then 15 mL of 0.2 mg / mL Ti3C2T x The dispersion was directly poured into the filtration device, and the filtration was continued for 10 minutes after the water was drained to make Ti3C2T x The nanosheets were adsorbed on the cellulose material with SiO2 attached. After filtration, they were vacuum dried at 50 °C for 3 h to obtain a circular triboelectric material (Ti3C2T x -SiO2-CFP, referred to as TS-CFP).

[0044] Comparative Example 1

[0045] (1) Take 0.6 mL of Ti3C2T with a concentration of 5 mg / mL x The dispersion was diluted to 0.2 mg / mL with deionized (DI) water.

[0046] (2) Place a qualitative filter paper with a diameter of 7 cm in a sand core funnel (the funnel diameter is 4 cm), turn on the vacuum pump switch, and then drip deionized water (DI) to make the qualitative filter paper and the sand core funnel tightly connected. Add 15 mL of Ti3C2T x The dispersion was directly poured into the filtration device, and the filtration was continued for 10 minutes after the water was drained to make Ti3C2T x The nanosheets were adsorbed on the cellulose material and dried under vacuum at 50 °C for 3 h to obtain a circular triboelectric material (Ti3C2Tx -CFP, abbreviated as T-CFP).

[0047] Example 2

[0048] Ti3C2T x -Assembly of SiO2-CFP-based TENG devices:

[0049] (1) Use a 7×7×0.5cm 3 Use a black sponge of the same size to bond two acrylic plates together, and stick a smaller one of the acrylic plates with a size of 4×4×0.3cm on the outer surface of one of the acrylic plates. 3 The above combination is called A-board.

[0050] (2) Place the above two types of acrylic plates (7×7×0.5cm 3 ,4×4×0.3cm 3 ) Take one piece each and stick them together face to face to form board B.

[0051] (3) The TS-CFP (prepared in Example 1, as the positive friction layer) with conductive adhesive on the back and the FEP film were cut into 2.5×2.5 cm 2 Squares were made and, after removing the release paper of the conductive adhesive, they were attached to the surfaces of small acrylic plates on plates A and B as positive and negative friction layers, respectively. Finally, they were fixed to the contact end of a linear motor (JZK-10, China) and the electrodes were connected with copper wires. The contact-separation frequency of the friction pair was controlled to be 2 Hz by adjusting the distance between the two plates (13 cm). At the same time, an electrometer (Keithley6514, USA) and a data acquisition card (NI-USB-6259, USA) were used to collect the electrical output signals in real time.

[0052] Comparative Example 2

[0053] Assembly of CFP-based TENG devices:

[0054] Same as Example 2, except that TS-CFP (prepared in Example 1) is replaced by CFP.

[0055] Comparative Example 3

[0056] Assembly of T-CFP-based TENG devices:

[0057] Same as Example 2, except that TS-CFP (prepared in Example 1) is replaced by T-CFP prepared in Comparative Example 1.

[0058] Example 3

[0059] Assembly of TENG device:

[0060] (1) Triboelectric materials (Ti3C2T x -SiO2-CFP) preparation method: the same as Example 1, the only difference is that the usage ratio of nano-SiO2 and deionized water is 0.0003mg:30mL.

[0061] (2) Ti3C2T x -Assembly of SiO2-CFP-based TENG device: same as Example 2.

[0062] Example 4

[0063] Assembly of TENG device:

[0064] (1) Triboelectric materials (Ti3C2T x -SiO2-CFP) preparation method: the same as Example 1, the only difference is that the usage ratio of nano-SiO2 and deionized water is 0.0015mg:30mL.

[0065] (2) Ti3C2T x -Assembly of SiO2-CFP-based TENG device: same as Example 2.

[0066] Example 5

[0067] Assembly of TENG device:

[0068] (1) Triboelectric materials (Ti3C2T x -SiO2-CFP) preparation method: the same as Example 1, the only difference is that the usage ratio of nano-SiO2 and deionized water is 0.00375 mg:30 mL.

[0069] (2) Ti3C2T x -Assembly of SiO2-CFP-based TENG device: same as Example 2.

[0070] Example 6

[0071] Assembly of TENG device:

[0072] (1) Triboelectric materials (Ti3C2T x -SiO2-CFP) preparation method: the same as Example 1, the only difference is that the usage ratio of nano-SiO2 and deionized water is 1.875 mg:30 mL.

[0073] (2) Ti3C2T x -Assembly of SiO2-CFP-based TENG device: same as Example 2.

[0074] Comparative Example 4

[0075] Preparation of TS-CFP:

[0076] (1) Use a rotary circle cutter to cut filter paper with a diameter of 7 cm into 4 cm diameter pieces, place them on the tray of a glue spreader, turn on the vacuum pump to adsorb the filter paper to fix it, set the rotation speed of the glue spreader to 500 rpm, the rotation time to 100 s, and the rotation acceleration to 50 rpm / s 2 .

[0077] (2) Use a 30 mL disposable sterile syringe to absorb the SiO2 (0.00025 mg / mL) dispersion and drop it on the center of the filter paper. Start the gel coater for spin coating.

[0078] (3) After the spin coating is completed, use another sterile syringe to draw Ti3C2T x (0.2mg / mL) solution was dropped in the center of the filter paper, and the glue machine was started for spin coating. After the spin coating time was up, the glue machine stopped working.

[0079] (4) The spin-coated sample was placed in a vacuum drying oven at 50°C and dried for 3 h. Finally, the triboelectric material (Ti3C2T x -SiO2-CFP, referred to as TS-CFP).

[0080] (5) After assembling it into TENG, the triboelectric performance was tested, and the charge density, short-circuit current, and open-circuit voltage were 3.20 nC / cm 2 , 6.47μA, 48.93V.

[0081] Comparative Example 5

[0082] Preparation of TS-CFP:

[0083] (1) Add nano-SiO2 to deionized water (DI) (the dosage ratio of nano-SiO2 to deionized water is 0.0075 mg:30 mL), and then use a cell disruptor to perform ultrasonic dispersion to obtain a SiO2 dispersion.

[0084] (2) Place a qualitative filter paper with a diameter of 7 cm in a sand core funnel (the funnel has a diameter of 4 cm), turn on the vacuum pump switch, take 30 mL of SiO2 dispersion and pour it directly into the filtration device. After the water is drained, continue to filter for 10 minutes to allow the SiO2 nanoparticles to adhere to the cellulose skeleton (qualitative filter paper) to obtain a cellulose material with SiO2 attached.

[0085] (3) Take 0.6 mL of Ti3C2T with a concentration of 5 mg / mL x Dispersion, dilute it to 0.2 mg / mL with deionized water DI. Then 15 mL of 0.2 mg / mL Ti3C2T xThe dispersion was directly poured into the filtration device, and the filtration was continued for 10 minutes after the water was drained to make Ti3C2T x The nanosheets were adsorbed on the cellulose material with SiO2 attached. After filtration, they were vacuum dried at 50 °C for 3 h to obtain a circular triboelectric material (Ti3C2T x -SiO2-CFP, referred to as TS-CFP).

[0086] (4) After assembling it into TENG, the triboelectric performance was tested, and the charge density, short-circuit current, and open-circuit voltage were 4.16 nC / cm 2 , 10.81μA, 92.58V.

[0087] Effect Example 1

[0088] 1. Performance measurement method:

[0089] (1) The chemical structure of the material was measured using a Fourier transform infrared spectrometer (Nicolet iS50, USA) with a test resolution of 0.4 cm -1 , the test wavelength range is 500~4000cm -1 .

[0090] (2) The morphology and microstructure were photographed using scanning electron microscopy (F16502, PHENOM, The Netherlands) and HRTEM (JEOL JEM-2100Plus, Japan).

[0091] (3) X-ray diffraction (Rigaku D / MAX 2500V, Japan) was used to analyze the crystal structure of the material using Cu Kα radiation. The operating voltage and current were 60 kV and 300 mA, respectively, and the scanning speed was 5°·min -1 .

[0092] (4) The structural characteristics of the material were analyzed using a laser Raman spectrometer (inVia Reflex, UK) with an excitation wavelength of 532 nm, a power of 50%, and an exposure time of 16 s.

[0093] (5) X-ray photoelectron spectroscopy (Thermo Scientific K-Alpha, USA) was used to analyze the chemical elements of the materials. The excitation source used was Al Kα rays (hv = 1486.6 eV), and the operating voltage and filament current were 12 kV and 6 mA, respectively.

[0094] (6) An isothermal surface potential decay measurement system was used to analyze the trap energy level distribution of the material. An electrometer (Trek 347, USA) and an active electrostatic probe (Trek-6000B-13C, Kelvin, USA) were used to measure the surface potential decay of the sample. The trap distribution characteristics of the sample were calculated based on the isothermal current decay theory (proposed by Simmons and Tam).

[0095] (7) The dielectric properties (dielectric constant, dielectric loss, and dynamic conductivity) of the materials were analyzed using a broadband dielectric constant tester (Concept 50, Novocontrol, Germany). The test temperature was 25°C and the test frequency was 10–10 7 Hz.

[0096] (8) The surface potential of the material was measured using a Kelvin probe force microscope (Bruker Dimension Icon, Germany) with a scanning range of 2 μm × 2 μm.

[0097] (9) The surface roughness of the material was measured using an atomic force microscope (BRUKER, USA) with a scanning range of 10 μm × 10 μm.

[0098] (10) The transmittance of the samples in the wavelength range of 200–850 nm was measured using an ultraviolet-visible near-infrared spectrometer (UV-3600 Plus, Japan).

[0099] Ti3C2T x The atomically thin nanosheet morphology and fast electron transfer behavior can transfer the surface charge to the interior of the triboelectric material, avoiding excessive accumulation of triboelectric charge on the surface and hindering the entry of other charges, allowing more triboelectric charge to be generated. However, charge dissipation and generation generally occur simultaneously, and the dynamic equilibrium charge density determines the triboelectric output. The present invention uses a vacuum-assisted filtration method to introduce SiO2 as a deep trap builder into Ti3C2T x Interface with cellulose filter paper, e.g. Figure 1 As shown ( Figure 1 a is the preparation flow chart, b is the bonding action diagram, and c is the charge transfer and storage diagram). x The hydroxyl groups in the sheets undergo condensation reactions to form strong bonds, making Ti3C2T xThe nanosheets are highly arranged along the plane direction and tightly stacked on the SiO2 nanoparticles. At the same time, the hydrogen bonding force between the SiO2 nanoparticles and the cellulose (qualitative filter paper) further enhances the structural stability of the composite film. As a typical inorganic electret, SiO2 causes defects on the surface due to the unsaturated oxidation of silicon or dangling bonds or unsaturated bonds during the oxidation process, resulting in sites in the material that allow carriers to stay. When the charge passes through the Ti3C2T x When the conductive network formed is transmitted to the internal space of the friction material, the deposited SiO2 layer acts as a trap for the triboelectric charge, providing conditions for charge accumulation. The increase in trap density and depth increases the probability of charge being captured during the migration process, effectively avoiding / reducing the rapid dissipation of triboelectric charge, thereby achieving the stability of charge retention. This is of great significance for enhancing the charge storage capacity of triboelectric materials and improving the electrical output performance of TENG. The specific results are as follows:

[0100] 2. Characterization results of defect status

[0101] (1) The qualitative filter paper (CFP), the T-CFP prepared in comparative example 1, and the triboelectric material (TS-CFP) prepared in example 1 were tested by infrared spectroscopy (FTIR) and energy dispersive spectroscopy (EDS). The results are shown in Figure 2 Figure a in .

[0102] from Figure 2 As can be seen in Figure a, compared with the unmodified cellulose (qualitative filter paper), the -OH characteristic peak of the cellulose filter paper (TS-CFP) modified with SiO2 increased from 3277 cm -1 Red shifted to 3255 cm -1 This phenomenon indicates the existence of strong hydrogen bonds in the material, which significantly improves the stability of the structure. At the same time, the characteristic peaks of Si-O-Si bond and Si-O bond of SiO2 and the peak at 546 cm -1 This provides strong evidence for the successful preparation of TS-CFP composite film (triboelectric material).

[0103] (2) X-ray diffraction (XRD) analysis was performed on the qualitative filter paper (CFP), the T-CFP prepared in Comparative Example 1, and the triboelectric material (TS-CFP) prepared in Example 1. The results are shown in Figure 2 Figure b.

[0104] from Figure 2 As can be seen in Figure b, relative to T-CFP, the (002) diffraction peak of TS-CFP shifts from 2θ=22.43° to 22.73°. This is because the introduction of SiO2 makes the cellulose-Ti3C2T xThe amount of amorphous skeleton increases, the symmetry of the molecular structure decreases, and more defects are formed, resulting in a decrease in crystallinity. x The characteristic diffraction peak shifted from 2θ=6.54° to 6.46°, indicating that the interplanar spacing became larger, indicating that the introduction of SiO2 effectively inhibited the Ti3C2T x The stacking of the sheets is conducive to the formation of a conductive network for charge transfer. Observation by high-resolution transmission electron microscopy (HRTEM) (TS-CFP prepared in Example 1 was added to deionized water, then ultrasonically dispersed, and the dispersion was dripped onto the copper mesh drop by drop. After natural drying, the morphology was photographed by HRTEM. The HRTEM image of the dispersion is shown in Figure 2 g diagram, regions 1 and 2 are Ti3C2T x and Ti3C2T x The morphology of the @SiO2 mixture and the corresponding lattice fringe spacing are shown in Figure h (i) and (ii). The results also illustrate this phenomenon. x The lattice fringe spacing of Ti3C2T increases from 0.258nm to 0.275nm, which suppresses the x The stacking of flakes promotes the formation of a conductive network, which facilitates the transfer of surface charges into the material.

[0105] (3) Determination of Raman spectra of the qualitative filter paper (CFP), T-CFP prepared in Comparative Example 1, and triboelectric material (TS-CFP) prepared in Example 1. The results are shown in Figure 2 Figure c.

[0106] from Figure 2 As can be seen in Figure c, 113cm -1 The peak at 378 cm is a unique sign in the Raman spectrum of cellulose (qualitative filter paper). At the same time, the two typical characteristic peaks of cellulose are located at 378 cm -1 and 1094cm -1 , corresponding to the symmetric bending vibration of the pyran ring (-CCC) and the stretching vibration of the -CO bond. Raman analysis shows that the vibration modes of these three peaks of TS-CFP are red-shifted compared with CFP and T-CFP. This red-shift is caused by the change of local stress or charge distribution caused by defects. In addition, the width of the peak has increased, especially in the low wave number region (150-400cm -1 ) characteristic peaks, which appear at 604cm -1 Ti3C2T x The characteristic peak red-shifted to 613 cm -1 The broadening of the peak further shows that the introduction of SiO2 does increase the defect density in the material to a certain extent.

[0107] (4) The XPS full spectra of the qualitative filter paper (CFP), T-CFP prepared in Comparative Example 1, and the triboelectric material (TS-CFP) prepared in Example 1 are shown in Figure 2 Figure d in .

[0108] from Figure 2 As can be seen in Figure d, TS-CFP has new peaks at 455.08eV and 155.08eV, corresponding to the binding energies of Ti 2p and Si 2p, respectively. This is because SiO2 and Ti3C2T x The introduction of TS-CFP results in defects in the sample that allow charge retention to varying degrees, leading to changes in bonding energy. Figure 2 Figure e) consists of five peaks: C=O, CO, CC, C-Si and C-Ti, located at 285.88, 284.78, 282.78, 281.78 and 279.88 eV, respectively. In particular, the C-Ti bond comes from Ti3C2T x , the representative peaks of C-Si bonds are SiO2 nanoparticles and Ti3C2T x The interaction between Si 2p spectrum ( Figure 2 The f-figure in Figure 2 shows three peaks, which are SiO at 107.48, 102.88 and 99.88 eV. 2.0 、SiO 1.5 and Si-C. SiO 2.0 The peaks confirm the presence of SiO2 in the product. In addition, the Si element of SiO2 nanoparticles is similar to that of Ti3C2T x The surface terminals (-O, -OH) of the sheets combine with C elements to form Si-C bonds and SiO 1.5 Si-O bond. Ti 2p spectrum ( Figure 3 ) fits three peaks, namely TiO2 (459.38 eV), TiO 2-X (454.48eV), Ti-C (453.38eV), further proving that SiO2 nanoparticles and Ti3C2T x The bonding between the sheets gives the entire triboelectric material structural stability during the contact-separation cycle, and also helps the transmission and storage of triboelectric charges to a certain extent.

[0109] Ti3C2T x -Storage performance of triboelectric charge of SiO2-CFP material (prepared in Example 1):

[0110] (1) After confirming the presence of a large number of traps in TS-CFP, the energy level density distribution of the traps (shallow traps and deep traps) in the material was evaluated. Specifically: the ISPD model is used to quantify the energy distribution of the traps in order to gain a deeper understanding of the surface trap state of the material sample. First, the corona charging method is used to inject charges into the material samples (qualitative filter paper (CFP), T-CFP prepared in Comparative Example 1, and triboelectric material (TS-CFP) prepared in Example 1), and the needle-plate electrode system with a gate electrode uniformly injects charges of the same polarity into the surface of the material sample through DC corona discharge. Among them, the diameter of the needle electrode is 1 mm, and the radius of curvature of the needle tip is about 13 μm. The gate acts as a clamp to limit the voltage, so that the charged ions generated by the discharge at the tip of the needle electrode migrate uniformly to the surface of the material sample, and the constant temperature metal platform is grounded as a plate electrode. Among them, the needle and gate electrodes are 8 mm apart, and the gate is placed 6 mm above the surface of the material sample. The surface potential attenuation of the material sample is measured using an electrostatic potentiometer and an active electrostatic probe, wherein the electrostatic probe is placed 3 mm above the surface of the material sample. After the external voltage is removed, the dynamic process of the surface potential decay of the material sample over time is monitored on the computer. The results are shown in Figure 4 Figure a.

[0111] from Figure 4 It can be seen from Figure a (normalized ISPD curve) that the introduction of SiO2 and Ti3C2T x The cellulose filter paper (TS-CFP) shows a low charge dissipation rate, which indicates that traps play a vital role in charge storage and can significantly improve the efficiency and stability of charge storage. Based on the isothermal current decay theory proposed by Simmons and Tam, the trap distribution characteristics of the material sample can be calculated. The experiment only considers the decay in the form of in vivo transport and ignores the migration of charge between deep and shallow traps. The trap energy level E in the material is T and the trapped charge density Q S They can be expressed as:

[0112] E T =k B Tln(vt) (1)

[0113]

[0114] In formula (1): k B is the Boltzmann constant; T is the absolute temperature, K; v is the frequency of escape attempts, approximately 10 12 s -1 The order of magnitude; t is the decay time;

[0115] In formula (2), t is the decay time; ε0 and ε r are the vacuum dielectric constant and relative dielectric constant respectively; e is the charge of the electron; is the surface potential; L is the sample thickness.

[0116] (2) The trap distribution characteristics obtained based on the normalized ISPD curves measured experimentally are shown in Figure 4 Figure b (shallow trap energy level distribution) and Figure c (deep trap energy level distribution), the trap density peaks in the figures represent the centers of shallow and deep traps, respectively.

[0117] Trap level density distribution ( Figure 4 Figures b and c) show that the introduction of Ti3C2T x The improvement of the trap density (shallow and deep traps) of the (T-CFP) material was not significant. On this basis, after further introducing the deep trap builder SiO2 nanoparticles, the shallow trap density of the triboelectric material (TS-CFP prepared in Example 1) increased from 0.169×10 21 eV -1 ·m -3 Increased to 2.723×10 21 eV -1 ·m -3 , increased by about 15 times, especially the deep well density from 0.020×10 21 eV -1 ·m -3 Increased to 1.089×10 21 eV -1 ·m -3 , an increase of about 53 times. The significant increase in deep trap density indicates that there are more such defects or areas inside the TS-CFP material, which increases the difficulty of charge detrapping, thereby directly improving the material's ability to capture charge. Therefore, during the contact charging process, more charges are captured by the deep traps and stored inside the material, which helps to increase the total amount of charge inside the material. More importantly, the increase in deep trap density causes the charge to stay inside the material longer, reducing the dissipation rate of triboelectric charge and further increasing the charge accumulation inside the material.

[0118] (3) In order to further demonstrate the inhibitory effect of deep traps on charge dissipation, the electrical properties of the materials under the action of an electric field were measured by dielectric properties test. The capacitance method was used to measure the capacitance of the material samples (qualitative filter paper (CFP), T-CFP prepared in Comparative Example 1, and triboelectric material prepared in Example 1 (TS-CFP)) at room temperature (25°C) for 10 to 10 7 Dielectric constant in the Hz frequency range ( Figure 4 d figure), dielectric loss ( Figure 4 e diagram) and conductivity ( Figure 4 f figure).

[0119] The size of the dielectric constant directly reflects the material's ability to store charge. Figure 4As can be seen in Figure d, the increase in frequency leads to a decrease in the dielectric constant of all materials. Under high frequency conditions, the dielectric constant of pure cellulose (qualitative filter paper) decreases to 2.32×10 2 , while TS-CFP can maintain up to 23.68×10 2 The dielectric constant of TS-CFP is about 10 times higher than that of CFP. This shows that TS-CFP material has a strong ability to store charge in an electric field. The dielectric constant represents the polarization degree of the dielectric, that is, the ability to bind charges. When the dielectric constant is large, the ability of the dielectric to bind charges is enhanced, thereby improving the charge storage capacity. And higher dielectric loss may increase leakage current and reduce the performance of TENG.

[0120] from Figure 4 As can be seen from the figure e, in the range of 10 to 10 7 In the external electric field frequency range of Hz, the dielectric loss of TS-CFP is the lowest. Charge dissipation is closely related to dielectric loss, because dielectric loss itself is the process in which charge flows and consumes electrical energy under the action of an electric field. The speed and degree of charge dissipation directly affect the magnitude of dielectric loss. Therefore, compared with cellulose (qualitative filter paper), TS-CFP with a higher dielectric constant and lower dielectric loss can effectively retain charge and reduce the charge dissipation rate. It is also more suitable for use as a triboelectric material for TENG to obtain higher triboelectric output performance.

[0121] from Figure 4 As can be seen from the figure f, the conductivity of CFP is the largest, followed by T-CFP, and TS-CFP is the smallest. This is due to the fact that Ti3C2T x The uneven dispersion in cellulose fibers easily forms agglomerates, which blocks the electron transmission path and reduces the conductivity of the material. x On the other hand, the stacking between the sheets increases the density of deep traps, which enhances the trap capture effect in the dielectric body. Since the escape from the deep traps requires overcoming a larger trap barrier, the number density and mobility of the migrating carriers are reduced, and the conductivity also decreases accordingly, which is conducive to the stable storage of triboelectric charges.

[0122] The surface of the material sample is scanned by the KPFM scanning probe, and the potential difference between the probe and the surface is measured to obtain an image of the surface potential distribution. The results are shown in Figure 4 G graph of .

[0123] from Figure 4As can be seen from the g diagram, TS-CFP has a larger surface potential than CFP and T-CFP. This is because the deep traps form a local low potential area, which promotes the enhancement of the charge capture effect, so that a large amount of positive charge is concentrated in the deep traps and their vicinity, ultimately leading to an increase in potential. This more intuitively proves the effect of deep traps in triboelectric materials on charge storage capacity (TS-CFP with deep traps has better charge storage capacity).

[0124] Effect Example 2

[0125] Ti3C2T x - Triboelectric output performance of SiO2-CFP-based TENG:

[0126] (1) The reduction of the charge dissipation rate of the friction layer is a key factor in achieving efficient and stable electrical output of TENG. In order to verify the improvement of electrical output by deep traps, the charge density, short-circuit current and open-circuit voltage of the material samples under the contact-separation cycle were tested using the devices prepared in Example 2 and Comparative Examples 2-3. The results are shown in Table 1. Figure 5 .

[0127] Figure 5 Figure a shows the charge density of different devices, Figure b shows the short-circuit current of different devices, and Figure c shows the open-circuit voltage of different devices.

[0128] from Figure 5 As can be seen from Figures a to c, compared with the CFP-based TENG (prepared in Comparative Example 2), the charge density of the TS-CFP-based TENG (prepared in Example 2) increases from 1.07 nC·cm -2 Increased to 7.21nC·cm -2 , an increase of 574%; short-circuit current increased from 2.44μA to 15.74μA, an increase of 545%; open-circuit voltage increased from 29.18V to 136.52V, an increase of 368%. These data show a huge improvement in triboelectric output. The reason is that SiO2 will be replaced by Ti3C2T x The friction charges transmitted by the conductive network into the material are effectively stored, which enhances the total charge density of the friction layer and thus improves the output voltage of TENG.

[0129] (2) The surface roughness (Rq) of different friction layers (Example 2 and Comparative Examples 2-3) was measured using an atomic force microscope (AFM). The results are shown in Figure 5 Figure d.

[0130] from Figure 5 As can be seen in Figure d, the Rq of TS-CFP is increased by 250% compared with cellulose (qualitative filter paper). ,This is because the introduction of SiO2 will form an uneven nanostructure on the fiber surface, and then the vacuum-assisted filtration process will have a great impact on the Ti3C2T x The thin sheets exert vertical forces, resulting in physical interactions between the dispersed components, making Ti3C2T x Tightly attached to the SiO2 nanoparticles, so they stack on each other in the vertical direction, this attachment process changes the flatness of the original surface, thereby increasing the roughness and, to a certain extent, improving the output of triboelectric charge on the material surface.

[0131] (3) The open circuit voltage of TS-CFP at different SiO2 addition amounts is shown in Figure 5 Figure e. In Figure e, CK is when the amount of SiO2 added is 0 (Comparative Example 1), A is when the amount of SiO2 added is 0.0003 mg (Example 3), B is when the amount of SiO2 added is 0.0015 mg (Example 4), C is when the amount of SiO2 added is 0.0075 mg (Example 1), D is when the amount of SiO2 added is 0.00375 mg (Example 5), and E is when the amount of SiO2 added is 1.875 mg (Example 6).

[0132] from Figure 5 As can be seen from Figure e, with the increase of SiO2 content, the output voltage of TENG shows a trend of first increasing and then decreasing. This is because TS-CFP doped with an appropriate amount of SiO2 has more deep wells, which prolongs the time that the friction charge stays inside the material and enhances the stability of the friction charge retention, thereby increasing the output voltage of TENG. However, the active silanol groups on the surface of SiO2 make it highly hydrophilic. When the SiO2 content continues to increase, the electret effect of SiO2 itself weakens. In addition, the concentration of surface active silanol groups will increase, resulting in enhanced hydrophilicity of the material. The water molecules adsorbed on the surface will significantly increase the conductivity, which will intensify the surface charge dissipation, which is very unfavorable for TENG.

[0133] (4) At a contact-separation frequency of 2 Hz, the output stability (mechanical durability of the device) of the TS-CFP-based TENG prepared in Example 2 was measured after 20k (twenty thousand) contact-separation cycles. The results are shown in Figure 5 f graph of .

[0134] from Figure 5 As can be seen from the figure f, after 20,000 contact-separation cycles, the TS-CFP-based TENG device still has a stable voltage output of up to 136 V, with almost no weakening.

[0135] (5) The output voltage of the TS-CFP-based TENG prepared in Example 2 at different contact and separation frequencies was measured. Figure 5 G graph of .

[0136] from Figure 5 As can be seen from the g graph, as the contact-separation frequency increases, the output voltage of TENG will also increase accordingly. However, when the frequency increases to a certain extent, the growth rate will slow down or even tend to saturation. This is because although the frequency change will cause the number of contact-separation cycles to change per unit time and cause the peak value of the output signal to change, the speed and efficiency of charge transfer are limited by many factors, so it does not have a fundamental impact on the basic process of triboelectric charging. Therefore, within the appropriate frequency range, TENG can maintain relatively stable output performance, which verifies that the triboelectric output of TS-CFP-based TENG has excellent mechanical stability.

[0137] (6) The instantaneous power density of the TS-CFP-based TENG prepared in Example 2 was calculated based on the peak output voltage and current values ​​measured using various external load resistances (i.e., 0.01 MΩ to 200 MΩ). Figure 5 The h-graph and Figure 6 , Figure 6 Where a is the change of output voltage with load resistance, and b is the change of current with load resistance.

[0138] from Figure 6 It can be seen that as the load resistance increases, the output voltage gradually increases, while the current decreases. Figure 5 As can be seen from the h figure, when the load is 6MΩ, the peak power density of the TS-CFP-based TENG is 0.688W·m -2 Compared with pure fiber-based TENG (0.011W·m -2 ), the peak output power of TS-CFP is increased by more than 61 times.

[0139] (7) The TS-CFP-based TENG prepared in Example 2 was connected to a full-wave bridge rectifier (to convert the AC output signal into a DC signal), and the generated DC output was used to charge various capacitors (0.47 μF, 1.0 μF, 2.2 μF, and 6.8 μF). The corresponding capacitor charging behaviors are shown in Figure 5 The i-picture.

[0140] from Figure 5 As can be seen from the figure, the TS-CFP-based TENG can charge a 6.8 μF capacitor to 1 V within 30 s. Therefore, the TS-CFP-based TENG prepared in Example 2 of the present invention can power low-power electronic devices or store them for subsequent use, showing great potential and broad application prospects in the field of energy harvesting.

[0141] Effect Example 3

[0142] Determination of Ti3C2T x-SiO2-CFP based TENG (prepared in Example 2, also called triboelectric humidity sensor) energy harvesting and wireless humidity sensing performance under hot conditions, the results are shown in Figure 7 , Figure 7 a is a schematic diagram of energy harvesting and humidity sensing of TS-CFP-based TENG under hot conditions, b is the voltage of CFP-based TENG under ultraviolet irradiation for different times, c is the voltage of TS-CFP-based TENG under ultraviolet irradiation for different times, d is the output voltage of TS-CFP-based TENG at different heating temperatures, e is the voltage of TS-CFP-based TENG under heating for different times at 230°C, f is the sensitivity of TS-CFP-based TENG as a sensor, g is the linear relationship between TS-CFP-based TENG and humidity, and h is the real-time output voltage of TS-CFP-based TENG.

[0143] (1) From Figure 7 As can be seen from Figure a, the TS-CFP-based TENG can realize energy harvesting under hot conditions and is expected to be used as a humidity sensor.

[0144] (2) From Figure 7 The b-graph and Figure 8 It can be seen that after 12 hours of UV irradiation, the voltage of CFP-based TENG and T-CFP-based TENG decreased by 88.7% and 52%, respectively. In contrast, the voltage of TS-CFP-based TENG decreased by only 14% ( Figure 7 This can be attributed to the significant absorption of UV light by the TS-CFP coating ( Fig. 9 ). More importantly, the deep traps can capture the photogenerated carriers generated by UV radiation, which enables the TENG to maintain a stable triboelectric output even after long-term UV irradiation.

[0145] (3) From Figure 7 As can be seen in Figure d, the voltage of the TS-CFP-based TENG initially increases, then decreases as the temperature increases, and finally stabilizes at about 161V. This is because the increase in temperature allows the deep traps to more effectively capture the additional charge carriers generated by thermal excitation. However, when the temperature is too high, the probability of the deep traps releasing the captured charges becomes too high, resulting in the inability to effectively retain the captured charges. In addition, the TS-CFP coating significantly enhances the thermal stability of the filter paper, allowing the friction nanogenerator to exhibit excellent environmental stability. Even at a temperature of 230°C for 12 hours, the voltage only dropped by 6% ( Figure 7 This discovery is crucial for self-powered micro-smart devices to maintain normal function under adverse weather conditions.

[0146] (4) From Figure 7As can be seen from the figure f, the TS-CFP-based TENG shows a short response-recovery time under contact-separation. From the time TS-CFP contacts another friction layer FEP, it takes only 32ms for its output signal to reach a stable state (the output voltage value reaches 136.5V). When the pair of friction layers begins to separate, it takes only 42ms for its output signal to recover to its original state, indicating the device's reaction speed and recovery ability under the contact-separation state, demonstrating its great potential as a sensor.

[0147] (5) Since water molecules easily interact with Ti3C2T x The hydrophilic groups on the surface produce hydrogen bonds, and the linear correlation index R between the output voltage and humidity of TS-CFP-based TENG is tested. 2 =0.992, reflecting the excellent sensitivity of the device to changes in humidity environment. Figure 7 G graph of .

[0148] from Figure 7 As can be seen from the h figure, the triboelectric performance of the TS-CFP-based TENG under different humidity conditions (real-time curve of the open circuit voltage during the humidification process (from 45% to 95% RH)) can maintain a voltage of about 25V at 95% relative humidity.

[0149] This further demonstrates that the TS-CFP-based TENG prepared in the present invention has excellent energy harvesting capability in hot environments and application potential for real-time monitoring of humidity changes.

[0150] In summary, the triboelectric material prepared by the present invention, namely TS-CFP, can accelerate charge transfer, while having charge retention stability, and achieves significant electrical output performance; relative to pure cellulose (qualitative filter paper), the normalized ISPD curve of TS-CFP shows a lower charge dissipation rate, the deep trap density increases by about 53 times, and the dielectric constant increases by about 10 times, showing excellent charge capture ability, effectively enhancing the ability to bind charges, thereby inhibiting charge migration and rapid dissipation. And the test found that the maximum output power density of TS-CFP-based TENG is more than 61 times higher than that of pure fiber-based TENG, and the charge density increases from 1.01nC·cm -2 to 7.21nC·cm -2, increased by 5.74 times, and the voltage output had almost no attenuation after 20,000 contact-separation cycles, and a 6.8μF capacitor could be charged to 1V within 30s. In addition, the voltage of the TENG prepared by the present invention only decreased by 14% and 6% respectively when exposed to ultraviolet light and high temperature for up to 12h. This is crucial for self-powered micro-intelligent devices to maintain normal functions under adverse weather conditions. In addition, by designing different humidity environments, it was found that the TS-CFP-based TENG prepared by the present invention has excellent humidity sensitivity (R 2 =0.992), and can maintain a voltage output of 25 V under humidity conditions up to 95% RH, demonstrating the high efficiency and stability of the TS-CFP-based TENG. In summary, this invention provides profound insights into the improvement of the triboelectric charge storage capacity of fiber-based triboelectric materials and reveals a promising strategy with broad implications for smart packaging systems.

[0151] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a triboelectric material, characterized in that: The following steps are involved: Attaching SiO2 to a cellulose skeleton to obtain a cellulose material attached with SiO2; Adding Ti3C2T to the cellulose material with SiO2 attached x The dispersion is dried to obtain the triboelectric material.

2. The preparation method according to claim 1, characterized in that: The method for attaching SiO2 to a cellulose skeleton comprises the following steps: SiO2 is added into water and dispersed by ultrasonic to obtain SiO2 dispersion liquid, the SiO2 dispersion liquid is poured on the cellulose material, and the cellulose material with SiO2 attached is obtained after suction filtration.

3. The preparation method according to claim 2, characterized in that: The SiO2 is nano-SiO2 with a particle size of 10 nm; The dosage ratio of SiO2 to water is 0.0075 mg:30 mL; the dosage ratio of SiO2 dispersion to the area of ​​cellulose material is 30 mL:12.56 cm 2 .

4. The preparation method according to claim 3, characterized in that: The SiO2 and Ti3C2T x Ti3C2T in dispersion x The mass ratio is 0.0075mg:3mg; the cellulose material includes filter paper.

5. A triboelectric material prepared by the preparation method according to any one of claims 1 to 4.

6. Use of the triboelectric material according to claim 5 in the preparation of a triboelectric nanogenerator.

7. A friction nanogenerator, characterized in that: The triboelectric material according to claim 5 is used as the friction layer.

Citation Information

Patent Citations

  • In-situ polymerized surface modified fiber-based friction nano-generator and preparation thereof

    CN108667339A

  • Wet friction material

    US20130037373A1